2015
DOI: 10.1007/s12035-015-9393-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Alpha-Linolenic Acid Supplement Alleviates Cognitive Impairment Correlate with Activating Hippocampal CREB Signaling in Natural Aging Rats

Abstract: Alpha-linolenic acid (ALA) is a major precursor of the essential n-3 polyunsaturated fatty acid (PUFA), whose deficiency alters the structure and function of membranes and induces cerebral dysfunctions. The major purpose of this study was to investigate the protective effect of prolonged ALA intake on cognitive function during natural aging. Female Sprague-Dawley rats aged 6 months were chronically treated with ALA and/or lard per day for 12 months. Regular diet-treated rats, both young and old (4 and 18 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…CREB activity and BDNF levels are associated with neurodegenerative diseases, because they play essential roles in acquisition learning and retention memory, as well as in activity‐dependent synaptic plasticity . In accordance with previous reports, the reduced hippocampal CREB activity and BDNF levels observed by us in HFD‐fed, aged rats coincided with impairments of spatial cognitive ability and synaptic plasticity. Importantly, MLT supplementation restored hippocampal CREB activity and BDNF levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CREB activity and BDNF levels are associated with neurodegenerative diseases, because they play essential roles in acquisition learning and retention memory, as well as in activity‐dependent synaptic plasticity . In accordance with previous reports, the reduced hippocampal CREB activity and BDNF levels observed by us in HFD‐fed, aged rats coincided with impairments of spatial cognitive ability and synaptic plasticity. Importantly, MLT supplementation restored hippocampal CREB activity and BDNF levels.…”
Section: Discussionsupporting
confidence: 92%
“…MWM tests were performed between 9:00 and 17:00, and conducted as described previously . Briefly, animals were pretrained (no platform) for 2 days to acclimatize to the water maze pool (diameter 150 cm, depth 50 cm, temperature 22 ± 1°C).…”
Section: Methodsmentioning
confidence: 99%
“…We additionally found that CDKL5‐dependent phosphorylation of SMAD3 does not directly affect SMAD3 activity, but that CDKL5 deficiency causes a reduction in SMAD3 protein levels and, consequently, in activity in Cdkl5 KO neurons. Phosphorylation at different sites of SMAD3 contributes to its stability . Most SMAD proteins can be polyubiquitinated and degraded in either a ligand‐dependent or a ligand‐independent manner .…”
Section: Discussionmentioning
confidence: 99%
“…63 Long-term dietary intake of ALA activates Akt signaling in the hippocampus of natural aging rats. 64 CREB is a transcription factor involved in critical functions such as neuronal plasticity and survival. CREB is phosphorylated at Ser133, and p-CREB is its active form.…”
Section: Discussionmentioning
confidence: 99%